CORRUPTION: CONCEPT, TYPES AND PHENOMENON - Ilkhomjon Turgunov (Western European Studies, 2024)
The article talks about corruption, which is one of the major problems of today. Corruption has a history of several thousand years. Written sources mention corruption in the period of the Sumerian kingdom before our era. The fact that corruption has reached our days shows that, like other vices, it cannot be completely eradicated. Even developed Arab countries could not get rid of corruption completely. However, the prevention of corruption, which threatens the development of society, and the fight against it, have always been continued in all countries on Earth. Many political scientists, researches, and scientific researches have been conducted in the fight against corruption. Many government and non-government programs are underway around the world, but success is still being sought. It talks about the essence of corruption and its types and appearance
Keywords: Corruption; society; state; bribery